Full-scale investigation of in-situ iron and alkalinity generation for efficient sulfide control. (15th December 2019) - Pikaar, Ilje; Flugen, Markus; Lin, Hui-Wen; Salehin, Sirajus; Li, Jiuling; Donose, Bogdan C.; Dennis, Paul G.; Bethke, Lisa; Johnson, Ian; Rabaey, Korneel; Yuan, Zhiguo
Abstract: Hydrogen sulfide induced corrosion of concrete sewer pipes is a major issue for wastewater utilities globally. One of the most commonly used methods to combat hydrogen sulfide is the addition of ferric chloride. While a reliable and effective method, ferric chloride is acidic causing OH&S concerns as well as alkalinity consumption in sewage. This study investigates, under full-scale field conditions, an alternative method for sulfide control by in-situ electrochemical generation of iron ions using sacrificial iron electrodes. This method concomitantly produces alkalinity through cathodic OH − generation, rather than consumption. The gaseous hydrogen sulfide concentrations at the discharge wet well of a real-life rising main (length: ∼1 km in, diameter: 150 mm) decreased from 173 ppm to 43 ppm (90 percentile of peak values), when a current of 0.86 A/m 3 of sewage was applied. The 90 percentile peak H2 S value was further reduced to 6.6 ppm when the applied current was increased to 1.14 A/m 3 sewage. Moreover, methane generation was almost completely inhibited from 25.3 ± 1.46 mg COD/L to 0.06 ± 0.04 mg COD/L. The overall cell voltage remained constant throughout the experimental period clearly showing the stability of the process. Detailed characterization of the down-stream sewer pipe biofilm revealed the complexity of the iron chemistry as the in-situ produced iron ions undergo transformation into a variety of iron species. Overall, this study demonstrates that in-situ generation of iron and alkalinity is an effective alternative method for hydrogen sulfide control in sewers. Graphical abstract: Image 1 Highlights: Full-scale demonstration of in-situ iron and alkalinity generation for H2 S control. Stable electrochemical performance achieved throughout the testing period. Near complete inhibition of sewer methane emissions was achieved. A variety of iron oxide species accumulated in the downstream sewer pipe biofilm.